2021
DOI: 10.1186/s13578-021-00691-5
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell interactome of human tooth germ from growing third molar elucidates signaling networks regulating dental development

Abstract: Background Development of dental tissue is regulated by extensive cell crosstalk based on various signaling molecules, such as bone morphogenetic protein (BMP) and fibroblast growth factor (FGF) pathways. However, an intact network of the intercellular regulation is still lacking. Result To gain an unbiased and comprehensive view of this dental cell interactome, we applied single-cell RNA-seq on immature human tooth germ of the growing third molar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…Regarding mouse, single-cell RNA-sequencing (scRNA-seq) datasets were generated from the constantly (re-)growing incisor and the more static, human-resembling molar at different timepoints, either of whole tooth or specific tissue components ( Sharir et al, 2019 ; Takahashi et al, 2019 ; Chen et al, 2020 ; Chiba et al, 2020 , 2021 ; Krivanek et al, 2020 ; Wen et al, 2020 ; Nagata et al, 2021 ; Zhao et al, 2021 ). Human sc transcriptomic data were predominantly generated from dental pulp and periodontal tissues of molars in both healthy and diseased states ( Krivanek et al, 2020 ; Pagella et al, 2021b ; Shi et al, 2021 ; Yin et al, 2021 ; Hemeryck et al, 2022 ; Lin et al, 2022 ; Opasawatchai et al, 2022 ). All these sc analyses generated deeper insight into the tooth molecular and cellular landscape, furthering the understanding of dental cell type heterogeneity and tooth biology.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding mouse, single-cell RNA-sequencing (scRNA-seq) datasets were generated from the constantly (re-)growing incisor and the more static, human-resembling molar at different timepoints, either of whole tooth or specific tissue components ( Sharir et al, 2019 ; Takahashi et al, 2019 ; Chen et al, 2020 ; Chiba et al, 2020 , 2021 ; Krivanek et al, 2020 ; Wen et al, 2020 ; Nagata et al, 2021 ; Zhao et al, 2021 ). Human sc transcriptomic data were predominantly generated from dental pulp and periodontal tissues of molars in both healthy and diseased states ( Krivanek et al, 2020 ; Pagella et al, 2021b ; Shi et al, 2021 ; Yin et al, 2021 ; Hemeryck et al, 2022 ; Lin et al, 2022 ; Opasawatchai et al, 2022 ). All these sc analyses generated deeper insight into the tooth molecular and cellular landscape, furthering the understanding of dental cell type heterogeneity and tooth biology.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the scRNA‐seq data, Notch3 was found as a marker for hDPSC, which was also identified by lineage tracing in mouse tooth injury model 35 . Furthermore, from scRNA‐seq analysis, the fate of hDPSC was possibly determined by the microenvironment it resided 30,32 . It is noteworthy that the cell population analysis on scRNA‐seq data showed that monolayer culture of hDPSCs was significantly different from freshly isolated hDPSCs in cellular composition 36 .…”
Section: Re‐analysis Of Oral Histological Structure and Histogenesis ...mentioning
confidence: 91%
“…Therefore, it is necessary to picture the comprehensive expression profiles of human teeth further by scRNA‐seq. The scRNA‐seq was used to discover the cellular heterogeneity and molecular signatures in human pulp 30–33 . From dynamics and differentiation trajectories analysis, endothelial cells exhibit the most dynamic behavior, while only minor differentiation trajectories are found in most dental pulp cell populations 31 .…”
Section: Re‐analysis Of Oral Histological Structure and Histogenesis ...mentioning
confidence: 99%
See 2 more Smart Citations